Advances on Defect Engineering of Vanadium‐Based Compounds for High‐Energy Aqueous Zinc–Ion Batteries. Issue 40 (26th August 2022) - Guo, Cong; Yi, Shanjun; Si, Rui; Xi, Baojuan; An, Xuguang; Liu, Jie; Li, Jingfa; Xiong, Shenglin
Abstract: Aqueous zinc–ion batteries (ZIBs) have been promptly developed as a competitive and promising system for future large‐scale energy storage. In recent years, vanadium (V)‐based compounds, with diversity of valences and high electrochemical‐activity, have been widely studied as cathodes for aqueous ZIBs because of their rich reserves and high theoretical capacity. However, the stubborn issues including low conductivity and sluggish kinetics, plague their smooth application in aqueous ZIBs. Among various countermeasures, defect engineering is believed as an effective method to alleviate the above limitations. This review highlights the challenges of different V‐based cathode materials (e.g., vanadium oxides and vanadates) and summarizes the advances in defect engineering strategies including types and effects of the defects, designed strategies, and characterization techniques for high‐energy ZIBs. Finally, several sound prospects in this fervent field are also rationally proposed for fundamental research and practical application. Abstract : Defects engineering is an effective method to alleviate typical issues of vanadium (V)‐based compounds for zinc–ion batteries (ZIBs), including low conductivity, sluggish diffusion kinetics, structural instability, and insufficient storage sites. This review highlights the challenges of different V‐based cathode materials and summarizes the advances in defect engineering including effects of the defects, designed strategies, and characterization techniques for high‐energy ZIBs.